STRATEGI NAFKAH PEREMPUAN SINGLE PARENT DALAM MEMPERTAHANKAN KESEJAHTERAAN KELUARGA - Susanti, Sri Desi; Hayat, Nurul (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Some fathers and mothers should carry out their role as parents and are also essential controllers to building a prosperous family in the family sphere. However, the occurrence of a life or death divorce causes the loss of the role of one parent, thus requiring a single parent to carry out both functions. In maintaining the welfare of their families, single parents carry out a livelihood strategy. This study aims to determine the family income strategy of single-parent women in preserving the welfare of their families in Kadugadung Village, Cipeucang District, and Pandeglang Regency. This study uses a qualitative approach with a descriptive method. The data collection technique uses observation, interview, and documentation techniques, with the focus of the research being on homemakers with single-parent status in Kadugadung Village. They play the role of homemakers while working to meet their lives and children's needs. This study's data sources are divided into two, namely primary and secondary. The results obtained are: 1) Single parent women in Kadugadung village, on average, work in the domestic environment to provide for the family, 2) The livelihood strategies used by single-parent women include active strategies, passive strategies, and network strategies, 3) The condition of single women's families Parents in the village of Kadugadung cannot be said to be prosperous because of low economic conditions so that they cannot fully meet the family's needs.